Synthesis and Characterization of (smif) 2M n (n = 0, M = V, Cr, Mn, Fe,Co, Ni, Ru; N = +1, M = Cr, Mn, Co, Rh, Ir; Smif =1,3-di-(2-pyridyl)-2-azaallyl) - Frazier, Brenda A.; Bartholomew, Erika R.; Wolczanski, Peter T.; Debeer, Serena; Santiago-Berrios, Mitk'El; Abruna, Hector D.; Lobkovsky, Emil B.; Bart, Suzanne C.; Mossin, Susanne; Meyer, Karsten; Cundari, Thomas R. (Inorganic Chemistry, 2011)
A series of Werner complexes featuring the tridentate ligand smif, that is, 1,3-di-(2-pyridyl)-2-azaallyl, have been prepared. Syntheses of (smif) M (1-M; M = Cr, Fe) were accomplished via treatment of M(NSiMe ) (THF) (M = Cr, n = 2; Fe, n = 1) with 2 equiv of (smif)H (1,3-di-(2-pyridyl)-2- azapropene); ortho -methylated ( Mesmif) Fe (2-Fe) and ( Me2smif) Fe (3-Fe) were similarly prepared. Metatheses of MX variants with 2 equiv of Li(smif) or Na(smif) generated 1-M (M = Cr, Mn, Fe, Co, Ni, Zn, Ru). Metathesis of VCl3(THF) with 2 Li(smif) with a reducing equiv of Na/Hg present afforded 1-V, while 2 Na(smif) and IrCl (THF) in the presence of NaBPh gave [(smif) Ir]BPh (1+-Ir). Electrochemical experiments led to the oxidation of 1-M (M = Cr, Mn, Co) by AgOTf to produce [(smif)2M]OTf (1+-M), and treatment of Rh (O CCF ) with 4 equiv Na(smif) and 2 AgOTf gave 1+-Rh. Characterizations by NMR, EPR, and UV-vis spectroscopies, SQUID magnetometry, X-ray crystallography, and DFT calculations are presented. Intraligand (IL) transitions derived from promotion of electrons from the unique CNC (nonbonding) orbitals of the smif backbone to ligand π*-type orbitals are intense (σ ≈ 10 000-60 000 M cm ), dominate the UV-visible spectra, and give crystals a metallic-looking appearance. High energy k-edge spectroscopy was used to show that the smif in 1-Cr is redox noninnocent, and its electron configuration is best described as (smif(-))(smif(2-))Cr(III); an unusual S = 1 EPR spectrum (X-band) was obtained for 1-Cr. © 2011 American Chemical Society.